Baicalin attenuated Mycoplasma gallisepticum‐induced immune impairment in chicken bursa of fabricius through modulation of autophagy and inhibited inflammation and apoptosis. (20th August 2020) - Ishfaq, Muhammad; Zhang, Wei; Liu, Yuhao; Wang, Jian; Wu, Zhiyong; Shah, Syed WA; Li, Rui; Miao, Yusong; Chen, Chunli; Li, Jichang
Abstract: BACKGROUND: Mycoplasma gallisepticum (MG) is the primary etiologic agent of chronic respiratory disease in poultry. However, the mechanism underlying MG‐induced immune dysregulation in chicken is still elusive. Baicalin shows excellent anti‐bacterial, anti‐inflammatory, anti‐carcinogenic and anti‐viral properties. In the present study, the preventive effects of baicalin against immune impairment in chicken bursa of fabricius (BF) were studied in an MG infection model. RESULTS: Histopathological examination showed increased inflammatory cell infiltrations and fragmented nuclei in the model group. Ultrastructural analysis revealed the phenomenon of apoptosis in bursal cells, along with the deformation of mitochondrial membrane and swollen mitochondria in the model group. However, these abnormal morphological changes were partially alleviated by baicalin. Meanwhile, baicalin treatment attenuated the level of proinflammatory cytokines, and suppressed nuclear factor‐kappa B expression at both protein and mRNA level. Terminal deoxynucleotidyl transferase‐mediated dUTP nick endlabeling assay showed extensive apoptosis in BF in the model group. The mRNA and protein expression levels of apoptosis‐related genes were upregulated in BF, while baicalin treatment significantly alleviated apoptosis in BF. In addition, alterations in mRNA and protein expression levels of autophagy‐related genes and mitochondrial dynamics proteins were significantly alleviated by baicalin. Moreover, baicalin treatment significantly attenuated MG‐induced decrease in CD8 + cells and reduced bacterial load in chicken BF compared to the model group. CONCLUSIONS: These results suggested that baicalin could effectively inhibit MG‐induced immune impairment and alleviate inflammatory responses and apoptosis in chicken BF. © 2020 Society of Chemical Industry